Optimizing dye wastewater treatment: The impact of operational flux in submerged anaerobic membrane bioreactor - Syed Saquib; Helen Julian; Sri Harjati Suhardi; Takahiro Watari; Takashi Yamaguchi; Tjandra Setiadi (South African Journal of Chemical Engineering, 2024)
The present study investigated the effect of operational flux on the performance of hollow fiber anaerobic membrane bioreactors (HF-sAnMBR) during treatment of synthetic wastewater containing diazo dye. Two extreme operational flux value, which were 56.92 LMH and 3.21 LMH in reactor 1 (R-1) and reactor 2 (R-2), respectively, were chosen and the systems were operated at an extended time of 128 days. Under high initial flux, total chemical oxygen demand (t-COD) and soluble chemical oxygen demand (s-COD) removal in HF-sAnMBR reached an average of 76.27 ± 3.26 % and 77.20 ± 2.97 %, respectively. In contrast, the AnMBR operated at a lower flux exhibited 62.91 ± 3.10 % t-COD and 65.56 ± 1.74 % s-COD removal. The mean decolorization was 82.88 ± 7.20 % and 76.18 ± 13.96 % in R-1 and R-2, respectively. While R-1 showed excellent performance from the first day of operation, R-2 required 60 days to achieve comparable performance. However, biofouling was aggravated in R-1, which led to frequent membrane cleaning. Despite the operational hurdles, the fast deposition of biofoulants on R-1 might be responsible for its high COD and color removal, as the microorganisms on the membrane surface actively degraded organics and dyes. UV–visible spectroscopy and gas chromatography-mass spectrometry analyses demonstrated the breakdown of azo bonds and further confirmed the presence of benzene-based aromatic intermediates and several mineralized byproducts. Microbial analysis revealed a shift at the community level, as the inoculum was abundant in the phylum Chloroflexi (48 %), which shifted to Firmicutes (R1:49 %; R2:46 %), with Clostridium as the major genus, which is attributed to azo dye-degrading bacteria. Anaerobic sulfate-reducing bacteria may contribute significantly to aromatic hydrocarbon degradation and further dye mineralization.